Longitudinal assessment of brainstem reflexes in Multiple Sclerosis compared to multimodal evoked potentials, MRI and clinical evaluations. Issue 3 (March 2016) - Magnano, I.; Pes, G.M.; Ginatempo, F.; Cabboi, M.P.; Pilurzi, G.; Tolu, E.; Conti, M.; Deriu, F.
Abstract : Background: We have previously shown in patients with relapsing-remitting Multiple Sclerosis (MS) that: ( i ) the vestibulomasseteric (VMR), acousticmasseteric (AMR), trigeminocollic (TCR) and vestibulocollic (VCR) reflexes are able to spot brainstem (BS) dysfunctions undetected by clinical and MRI examinations; (ii) the combined use of these Brainstem Reflexes (BSRs) with multimodal Evoked Potentials (EPs) is more valuable than each single test in the early years after onset. Our aim was to document BS changes over time by BSRs, EPs, MRI and BS signs/symptoms (CLIN) before and after at least one year follow up, in MS. Methods: Forty-five MS patients (34.8 ± 8.6 yrs old; disease duration 8.9 ± 6.6 yrs) underwent BSRs, EPs (namely Brainstem Auditory Evoked Potentials – BAEPs, median and tibial Somatosensory Evoked Potentials-mSEPs and tSEPs), MRI and CLIN examination. BSR and EP data were ranked and summed up to obtain a cumulative score expressing severity of neurophysiological impairment. Before-after changes were tested with Wilcoxon test. Results: After 15.1 ± 4.2 months from initial evaluation, no relapses had been reported by any patient. This was in line with the stability of the frequency of CLIN and MRI abnormalities (37.3% and 71.1%, respectively) at the follow up. Despite this, BSRs and EPs revealed a worsening of BS function. In particular, although the proportion of altered BSRs did not change significantly (80.6% vs 90.3%; p = 0.180), a significant worsening of scores was observed for VMR ( p = 0.001), AMR (0.018) and TCR ( p = 0.013). Similarly to BSRs, the incidence rate of EP abnormalities did not increased significantly (84.4% vs 86.7%, p = 0.564), but the analysis of cumulative score showed a significant worsening for the whole EP set ( p = 0.03) as well as for median SEP (68.9% vs 75.6%, p = 0.03), P14 mSEP (33.3% vs 51.1%, p = 0.005), tibial SEP (60% vs 66.7%, p = 0.03). Conclusions: BSRs and EPs were able to reveal a significant worsening of BS functions in spite of any variation of both BS signs/symptoms and of MRI BS lesion load. This is in agreement with previous reports on BSR/EP ability to detect clinically and radiologically silent BS lesions. Further studies are needed in a larger cohort of patient to assess BSR clinical usefulness in a longitudinal perspective. FISM GRANT 2011/R/17.